Comparison of joint load, motions and contact stress and bone‐implant interface micromotion of three implant designs for total ankle arthroplasty. (August 2022) - Zhang, Yanwei; Chen, Zhenxian; Zhao, Hongmou; Zhao, Dahang; Zhang, Xuan; Ma, Xin; Jin, Zhongmin
Highlights: The patient-specific musculoskeletal multibody dynamics model and finite element analysis were combined. The biomechanics of total ankle arthroplasty were calculated under walking conditions of three patients. For the first time, the biomechanical differences between INBONE II, INFINITY, and an anatomic ankle implant were compared. The anatomic implant could resume normal ankle motions, achieve reasonable stress and decrease bone-implant micromotion. The fixation design of INFINITY could decrease the bone-implant micromotion. Abstract: Background and Objective: Loosening and wear are still the main problems for the failure of total ankle arthroplasty, which are closely related to the micromotion at the bone-implant interface and the contact stress and joint motions at the articular surfaces. Implant design is a key factor to influence the ankle force, motions, contact stress, and bone-implant interface micromotion. The purpose of this study is to evaluate the differences in these parameters of INBONE II, INFINITY, and a new anatomic ankle implant under the physiological walking gait of three patients. Methods: This was achieved by using an in-silico simulation framework combining patient-specific musculoskeletal multibody dynamics and finite element analysis. Each implant was implanted into the musculoskeletal multibody dynamics model, respectively, which was driven by the gait data to calculate ankle forces and motions. These were then used as the boundary conditions for the finite element model, and the contact stress and the bone-implant interface micromotions were calculated. Results: The total ankle contact forces were not significantly affected by articular surface geometries of ankle implants. The range of motion of the ankle joint implanted with INFINITY was a little larger than that with INBONE II. The anatomic ankle implant design produced a greater range of motion than INBONE II, especially the internal-external rotation. The fixation design of INFINITY achieved lower bone-implant interface micromotion compared with INBONE II. The anatomic ankle implant design produced smaller contact stress with no evident edge contact and a smaller tibia-implant interface micromotion. In addition, significant differences in the magnitudes and tendencies of total ankle contact forces and motions among different patients were found. Conclusions: The articular surface geometry of ankle implants not only affected the ankle motions and contact stress distribution but also affected the bone-implant interface micromotions. The anatomic ankle implant had good performance in recovering ankle joint motion, equalizing contact stress, and reducing bone-implant interface micromotion. INFINITY's fixation design could achieve smaller bone-implant interface micromotion than INBONE II.